Pentingnya Pelayanan Perlawatan Pendeta Jemaat - Telly Manueke; Beni Chandra Purba; Budi Kelana (PT. Penerbit Tiga Mutiara, 2024)
Life within a congregation has its own dynamics that can be observed in the relationship between congregation members and the pastor. One important aspect to be discussed in this paper is the pastoral care provided by the pastor as the shepherd of the congregation. Pastoral care is one form of service that demonstrates the pastor's concern for the members of the congregation. In pastoral care, the pastor can listen, provide advice, and strengthen the faith of congregation members through visits, conversations, and prayer. Although time for preaching is limited, pastoral care has its own power to strengthen the hearts of congregation members. However, unfortunately, the importance of pastoral care is no longer clearly evident in some congregations, where some pastors no longer engage in pastoral care as they should.